THE RHETORICAL IDENTITY CONSTRUCTION OF ENGLISH INSTRUCTORS IN ONLINE ENGLISH COURSES ADVERTISEMENTS - Tanasale, Inggrit (LLT Journal: A Journal on Language and Language Teaching, 2021)
The superior image of native English teachers portrayed in ELT professionalism has been heavily criticized among scholars by raising awareness on the expertise than nativeness or races. However, the study is scarce regarding how online discourse such as web-based advertisement of English language courses rhetorically depicts their language instructors: a native speaker and local teachers. To fill this gap, the purposes of this study are to examine the attributes of language instructors and any potential discriminatory or privileged presentation evoke in the online ads. The initial analysis was done within twenty English course sites to view overall trends of English instructors' attributes in several websites in Indonesia. I then closely explored two websites, WSE and TBI, and how they textually and visually privilege and discriminate the competences of native English teachers or local teachers. The result shows the dominant rhetoric of native English teachers as English language experts. The findings of this study reveal that despite the scholarly effort to challenge native English speaker/teacher orientation, the educational institutions still perpetuate the hegemony of native speakers as the ideal model in English within online platforms.